1992
DOI: 10.1104/pp.100.3.1354
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Concentration and Transport in Genetic Lines of Pea

Abstract: Effects of the Na and Le loci on gibberellin (GA) content and transport in pea (Pisum sativum L.) shoots were studied. GA1, GA8, GA17, GA19, GA20, GA29, GA44, GA8 catabolite, and GA29 catabolite were identified by full-scan gas chromatography-mass spectrometry in extracts of expanding and fully expanded tissues of line C79-338 (Na Le). Quantification of GAs by gas chromatography-singleion monitoring using deuterated internal standards in lines differing at the Na and Le alleles showed that na reduced the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 28 publications
2
68
0
1
Order By: Relevance
“…4,5 The transport of active GAs and their intermediates was supported by grafting experiments . 6,7,8 The contradictory results obtained from different experiments could not pin-point the site of synthesis of bioactive GA. Gibberellins being synthesized via the terpenoid pathway, require 3 enzymes viz., terpene synthase (TPSs), cytochrome P450 mono-oxygenase (P450s) and 2-oxoglutarate dependent dehydrogenase (2 ODDs), for the biosynthesis of bioactive GA from GGDP in plants (Fig. 1).…”
Section: Gibberellin Biosynthesismentioning
confidence: 99%
“…4,5 The transport of active GAs and their intermediates was supported by grafting experiments . 6,7,8 The contradictory results obtained from different experiments could not pin-point the site of synthesis of bioactive GA. Gibberellins being synthesized via the terpenoid pathway, require 3 enzymes viz., terpene synthase (TPSs), cytochrome P450 mono-oxygenase (P450s) and 2-oxoglutarate dependent dehydrogenase (2 ODDs), for the biosynthesis of bioactive GA from GGDP in plants (Fig. 1).…”
Section: Gibberellin Biosynthesismentioning
confidence: 99%
“…Grafting is widely established in agriculture and provides practical advantages for vegetable production by increasing resistance to soilborne pathogens [1]- [4], tolerance to low root-zone temperatures [5]- [7], salinity tolerance [8]- [10], and endogenous hormone production [11]- [13]. In particular, increased salinity tolerance improves fruit yield of grafted tomato [8] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Proebsting et al (1992) reported that the biologically inactive precursor GA 20 , a product of the GA 20-oxidase, is the major transported GA from leaves to apices in pea.…”
Section: Results and Discussion Cucumber Female Flower Developmentmentioning
confidence: 99%